1923 N.H. Laws 138, § 2 - (:unkn) unknown (My University, 1923)
§If any person shall commit or attempt to commit a crime when armed with a pistol or revolver, and having no permit to carry the same, he shall in addition to the punishment provided for the crime, be punished by imprisonment for not more than five years.
Keywords: COMMITTING CRIME W/ WEAPON